2020
DOI: 10.1177/2325967119898125
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Knot Suture Anchor Versus Knotless Suture Anchor Technique for Anterior Talofibular Ligament Repair: A Biomechanical Comparison

Abstract: Background: To date, there are few biomechanical studies comparing the strength between knot repair and knotless repair procedures for anterior talofibular ligament (ATFL) injury. Purpose: To perform a biomechanical comparison of the strength of the arthroscopic ATFL repair technique with knot or knotless suture anchors in a cadaveric model with partial or complete ATFL injuries. Study Design: Controlled laboratory study. Methods: A total of 24 fresh-frozen cadaveric ankles were used. Arthroscopy was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Although there is concern regarding the strength of single knotless suture anchor repairs, a biomechanical study indicated an equivalent biomechanical strength between the knotless and knotted repair of ATFL injury. 34 Another biomechanical study reported that the single suture anchor repair at the distal fibular yields comparable strength and stiffness to that of the suture-only Broström repair. 35 In essence, the advantages of using a single knotless suture anchor outweigh any theoretical risks of this repair technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is concern regarding the strength of single knotless suture anchor repairs, a biomechanical study indicated an equivalent biomechanical strength between the knotless and knotted repair of ATFL injury. 34 Another biomechanical study reported that the single suture anchor repair at the distal fibular yields comparable strength and stiffness to that of the suture-only Broström repair. 35 In essence, the advantages of using a single knotless suture anchor outweigh any theoretical risks of this repair technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although the long-term outcomes of knot versus knotless suture anchors for this type of repair is unknown, the use of knotless sutures has shown equal or greater biomechanical strength for various orthopaedic pathologies. 17 , 18 Furthermore, knotless suture anchors reduce complications including patient discomfort, knot loosening, or knot migration. 17 Another advantage of this technique is the use of a single portal for both repairs instead of creating an additional portal for biceps tenodesis or transitioning to an open tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Furthermore, knotless suture anchors reduce complications including patient discomfort, knot loosening, or knot migration. 17 Another advantage of this technique is the use of a single portal for both repairs instead of creating an additional portal for biceps tenodesis or transitioning to an open tenodesis. This method overall reduces the risk of neurovascular injury, the risk of infection, and the recovery time for the patient.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 44 Knotless suture anchors have also shown decreased variability in biomechanical properties and greater than or equal to biomechanical strength vs traditional suture anchors, offering a more consistent biomechanical outcome compared to knot repair. 45 , 46 Furthermore, given the variety and complexity of repairs with excellent outcomes, the technique presented in this note reduces steps, tools, implants, and time to perform the repair, while offering a similar high-quality repair. For instance, this technique simultaneously passes sutures through the tendon and places the anchor into the lesser tuberosity, eliminating the use of traditional suture passers that are typically needed to pass sutures through the tendon.…”
Section: Discussionmentioning
confidence: 99%
“… 36 The use of a knotless suture anchor reduces complications associated with patient discomfort, knot migration, knot impingement, and chondral abrasion. 45 , 47 , 48 This surgical technique effectively reduces difficulties associated with traditional suture anchors and knot repairs, offers strong fixation and biomechanical performance, and minimizes both operative time and potential postoperative complications.…”
Section: Discussionmentioning
confidence: 99%